Manufacturing hollow obturator with resilient denture liner on post hemimaxillectomy - Michael Josef Kridanto Kamadjaja (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
A resilient denture liner is placed in the part of the hollow obturator base that contacts to post hemimaxillectomy mucosa. Replacing the resilient denture liner can makes the hollow obturator has an intimate contact with the mucosa, so it can prevents the mouth liquid enter to the cavum nasi and sinus, also eliminates painful because of using the hollow obturator. Resilient denture liner is a soft and resilient material that applied to the fitting surface of a denture in order to allow a more distribution of load. A case was reported about using the hollow obturator with resilient denture liner on post hemimaxillectomy to overcome these problems.